Measuring the factors influencing entrepreneurial e-Commerce growth in Saudi Arabia (I.S. Success factors & Demographics measurements) - Almehmadi, Bander (2010)
The construction of an evaluation mechanism for entrepreneurial e-Commerce projects can be foreseen as vital to help tolerate any obstacles or source of failure that might arise in the path of the new business. Establishing a framework that encapsulates all crucial factors is a mandatory requirement in this evaluation process in order to set standers by which a firm could measure its success ability and predict and reveal all bottlenecks by carrying a full proactive inspection rather than taken by surprise. This dissertation investigates the factors that are acting as stimulators to expand entrepreneurial e-Commerce activity amongst Saudis in the Arabian market. Based on a quantitative survey by way of a structured questionnaire, this study identifies (through factor analysis) the important factors that are impacting on rapid growth/development among entrepreneurial e-Commerce business in Saudi Arabia. The study also uses descriptive statistics to establish the level of the gap between the importance of these factors (as perceived by consumers).